Across community barriers: female characters in Vimala Devi’s short stories - Cielo Griselda Festino (Acta Scientiarum. Language and Culture, 2019)
This article brings a reading of the short-story collection Monção [Monsoon] ( 2003) by the Goan writer Vimala Devi (1932-). The collection can be read as a short-story cycle, a group of stories related by locality, Goa, character, Goans, from all walks of life, and theme, in particular women´s milieu, among other literary categories. In her book, written from her self-imposed exile in Portugal, Devi recreates Goa, former Portuguese colony, in the 1950s, before its annexation to India. A member of the Catholic gentry, Devi portrays the four hundred years of conflictive intimacy between Catholics and Hindus. Our main argument is that Devi´s empathy for her culture becomes even more explicit in Monção when her voice becomes one with that of all her women characters. Though they might be at odds, due to differences of caste, class and religion, Devi makes a point of showing that they are all part of the same cultural identity constantly remade through their own acts of refusal and recognition. This discussion will be framed in terms of Sidonie Smith and Julia Watson’s theory of autobiography (2001) as well as the studies on Goan women by the Goan critics Propércia Correia Afonso (1928-1931), Maria Aurora Couto (2005) and Fátima da Silva Gracias (2007).